Self-image and moral balancing: An experimental analysis - Ploner, Matteo; Regner, Tobias (Journal of economic behavior & organization, 2013)
•We experimentally investigate dynamic aspects of moral behavior.•Our design endogenously manipulates subjects’ moral self-image.•A self-reported die roll determines the endowment in a subsequent dictator game.•A low moral self-image (due to cheating) fosters generosity in the dictator game.•Moral balancing appears to be an important determinant of behavior. In our experiment, a dictator game variant, the reported outcome of a die roll determines the endowment (low/high) in a subsequent dictator game. In one treatment the experimenter is present and no cheating is possible, while in another subjects can enter the result of the roll themselves. Moral self-image is also manipulated in the experiment preceding ours. The aim of this experimental set up is to analyze dynamic aspects of moral behavior. When cheating is possible, substantially more high endowments are claimed and transfers of high-endowed dictators are bigger than when cheating is not possible (mediated by the preceding moral self-image manipulation). The preceding manipulations also have a direct effect on generosity, when subjects have to report the roll of the die truthfully. Moral balancing appears to be an important factor in individual decision making.